(untitled) (Update Dental College Journal, 2024)
Background: The purpose of a fixed prosthodontic treatment may vary from the restoration of a single tooth to the complete rehabilitation of full occlusion. Finish line design is important in any tooth preparation, as finish line ensures the success of the future prosthesis. Finish line affects not only retention but also stability of fixed prosthesis. The finish line must be distinct, uniform, and smooth. Finish line is important during tooth preparation for acceptable marginal adaptation. The finish line must be easy to prepare, it must be easy to duplicate in impression, conservative, and provide sufficient strength to restore material. Finish line design helps in measuring the surface detail recording ability of an impression material. Various tooth preparation designs have distinct finish lines. Objectives: To evaluate the finish line of the die in a fixed prosthodontic laboratory. Materials and Methods: This laboratory based descriptive, cross-sectional, observational study has been conducted in the department of prosthodontics, BSMMU, with a sample size of 125 working casts die having different finish lines. The purpose of this study was to observe the finish line of the die of the working cast by using a dental magnifying loop. Data was collected on the basis of type, location, and quality of the finish line and recorded on a predesign data collection sheet. Collected data were analyzed by using the chi-square test. A P-value <0.05 is considered statistically significant. Result: Among 125 dies, according to location of finish line maximum number of dies 110 (88%) were showed sub gingival finish line but according to types of finish line 112 (88.40%) dies were showed chamfer finish line and according to quality of finish line 105 (84%) dies were showed detectable finish line. Conclusion: According to the results of the study, it can be concluded that the tooth preparation for single crown that have been done in the department of prosthodontics, BSMMU most of their finish line is sub gingival, chamfer and detectable. Update Dent. Coll. j: 2024; 14(2): 9-14